Enhancing evidence-based practice into healthcare: Exploring the role of scientific skills in occupational therapists- - Desirée Valera-Gran; Irene Campos-Sánchez; Daniel Prieto-Botella; Paula Fernández-Pires; Miriam Hurtado-Pomares; Iris Juárez-Leal; Paula Peral-Gómez; Eva María Navarrete-Muñoz (Scandinavian Journal of Occupational Therapy)
Background Research utilization and evidence-based practice (EBP) in occupational therapy rely on essential scientific skills. Despite prior research exploring factors influencing EBP, a gap remains in understanding the specific scientific competencies crucial for effective EBP application.Objectives To (1) describe the level of scientific skills for EBP and research application, and (2) investigate the factors influencing higher scientific competence among 1159 Spanish-speaking occupational therapists.Material and Methods We assessed the scientific skills using the HACTO-Screen online survey. Recruitment was conducted through a non-probability convenience sampling method between April to June 2020, using social networks and email dissemination to education and professional organizations in Spain and Spanish-speaking Latin American countries.Results Out of a total score of 115 points, participants showed a moderate level of scientific skills (mean: 62.7, SD: 21.6), with literature searching skills ranking the highest and scientific writing skills ranking the lowest. Associations were found between greater scientific competence and advanced degrees, ongoing research training, and on-the-job research.Conclusions Continuous research training, higher academic degrees, and active research engagement are essential for enhancing scientific competence among occupational therapists.Significance Targeted training to enhance scientific skills and promote research utilization are crucial in advancing EBP in occupational therapy.